The Augmented Educator: Decolonial Psychological Capital for EFL Teachers in the GenAI Era - Sahril Nur; Auliyanti Sahril Nurfadhilah; Muhammad Safar Nur (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2026)
The rapid integration of Generative Artificial Intelligence (GenAI) into higher education has raised new concerns for English as a Foreign Language (EFL) lecturers, particularly anxiety about professional value, pedagogical authority, and teacher identity. This explanatory sequential mixed-methods study examined how a culturally anchored professional development intervention could reduce AI-Induced Professional Anxiety (AIPA) and strengthen Teacher Psychological Capital (PsyCap). Twenty-five EFL lecturers who were also doctoral students participated in a 12-week Augmented Educator intervention grounded in Bugis-Makassar values: Sappa, Amaccang, and Siri' na Pacce. Quantitative data were collected using an adapted AIPA scale and a culturally adapted Teacher-PsyCap questionnaire, while qualitative data were drawn from reflective journals and interviews with eight participants. The findings showed a significant reduction in professional anxiety and notable gains in self-efficacy, resilience, hope, and optimism. The qualitative results further indicated that participants began to view AI not as a replacement for teachers, but as a tool requiring human judgment, cultural interpretation, and ethical guidance. The study argues that AI-related teacher development should move beyond technical training and include culturally meaningful psychological support for sustaining teacher agency in the GenAI era.